Four novel single nucleotide Polymorphisms within the promoter region of p53 gene and their associations with uterine leiomyoma - Hsieh, Yao-Yuan; Wang, Jui-Ping; Lin, Chich-Sheng (My University, 2007)
Dysregulated p53 expression has been implicated as a major contributor to numerous tumorigenesis. Single nucleotide polymorphisms (SNPs) within the functional consequence of the novel p53 promoter region remains obscure. Herein, we aimed to establish the extent of genetic variability within the promoter region of p53 gene as well as their association with leiomyoma susceptibility. Women were divided into two groups, leiomyoma (n = 160) and nonleiomyoma controls (n = 200). Total DNA was isolated from the peripheral blood of subjects. The DNA fragment containing p53 promoter regions (+64 similar to -404 bp) were obtained by amplification of polymerase chain reaction. The variations of DNA fragments were detected by DNA sequencing or restriction fragment length polymorphism (RFLP). Sequence alignment was used to identify sequence variations in p53 promoter regions. Genotypes were analyzed by method of RFLP. Genotypes/allelic frequencies in the leiomyoma and control groups were compared. A total of 15 sequence variations within p53 promoter region were identified, including -408 T/C, -382 A/G, -359 A/G, -325 T/C, -250 A/G, -216T/C, -205G/A, -198G/A, -177T/C, -103A/ G, -81 G/A, -71 G/A, -51 T/A, -33 A/G, and -17 T/ C. Among these variations, four SNPs (-250 A/G, -216 T/C, -103 A/G, and -33 A/G) were established. Allele frequencies of -250(star)G/-216(star)C/ -103(star)G/-33(star)G in the leiomyoma group and control group 6.9/5.0/5.9/3.8% and 3.8/1.8/2.3/4.0%, respectively. Two of them (-216(star)C and -103(star)G) are associated with higher leiomyoma susceptibility. We concluded that some sequence variations were observed within the promoter region of p53 gene. The SNPs of -216(star)C and -103(star)G among the identical sequence variations are associated with leiomyoma development.
Keywords: leiomyoma; p53; p53 promoter; polymorphism; SNP